ANALISIS PENGENDALIAN BAHAN BAKU PADA PRODUKSI PT KONIMEX SUKOHARJO - Ryan Budi Prakoso; Pardi Pardi (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
This study intends to confirm the policies and strategies for controlling raw materials applied at PT Konimex. The method in this research is qualitative, examining the condition of the object that is natural or in accordance with the actual conditions and the researcher is the main tool. The data was obtained by using the triangulation method of sources, derived from 3 different sources but with the same technique, namely in-depth interviews. Data analysis technique by combining data related to raw material control, explaining raw material control at PT Konimex, then evaluating according to existing theory in terms of control environment, control activities, risk assessment, information and communication, and monitoring. The results of the research, namely the control of raw materials at PT Konimex there are still weaknesses in the information and communication components and monitoring. Information regarding the procurement of raw materials needs to be updated in accordance with the latest production plan and monitoring related to the procurement of raw materials needs to be carried out regularly so that excess stock of raw materials does not occur and causes the production process to be hampered.